Characterization of RPC operation with new environmental friendly mixtures for LHC application and beyond. (29th July 2016) - Guida, R.; Capeans, M.; Mandelli, B.
Abstract: The large muon trigger systems based on Resistive Plate Chambers (RPC) at the LHC experiments are currently operated with R134a based mixture. Unfortunately R134a is considered a greenhouse gas with high impact on the enviroment and therefore will be subject to regulations aiming in strongly reducing the available quantity on the market. The immediat effects might be instability on the price and incertitude in the product availability. Alternative gases (HFO-1234yf and HFO-1234ze) have been already identified by industry for specific applications as replacement of R134a. Moreover, HFCs similar to the R134a but with lower global warming potential (GWP) are already available (HFC-245fa, HFC-32, HFC-152a). The present contribution describes the results obtained with RPCs operated with new enviromemtal friendly gases. A particular attention has been addressed to the possibility of maintening the current operation conditions (i.e. currently used applied voltage and front-end electronics) in order to be able to use a new mixture for RPC systems even where the common infrastructure (i.e. high voltage and detector components) cannot be replaced for operation at higher applied voltages.